Rigorous mathematical thinking : conceptual formation in the mathematics classroom - Kinard, James T., 1943- (Cambridge University Press, 2008)
This book demonstrates how rigorous mathematical thinking can be fostered through the development of students' cognitive tools and operations. Though this approach can be applied in any classroom, it seems to be particularly effective with socially disadvantaged and culturally different students. The authors argue that children's cognitive functions cannot be viewed as following a natural maturational path: They should be actively constructed during the educational process. The Rigorous Mathematical Thinking (RMT) model is based on two major theoretical approaches that allow such an active construction of cognitive functions: Vygotsky's theory of psychological tools and Feuerstein's concept of mediated learning experience. The application of the RMT model in various urban classrooms demonstrates how mathematics education standards can be reached even by students with a history of educational failure who were considered hopeless underachievers."--BOOK JACKET.